2021
DOI: 10.1523/jneurosci.0346-21.2021
|View full text |Cite
|
Sign up to set email alerts
|

α2δ-1–Dependent NMDA Receptor Activity in the Hypothalamus Is an Effector of Genetic-Environment Interactions That Drive Persistent Hypertension

Abstract: The interplay between genetic and environmental factors is critically involved in hypertension development. The paraventricular nucleus (PVN) of the hypothalamus regulates sympathetic output during stress responses and chronic hypertension. In this study, we determined mechanisms of synaptic plasticity in the PVN in chronic stress-induced persistent hypertension in male borderline hypertensive rats (BHR), the first offspring of spontaneously hypertensive rats and normotensive Wistar-Kyoto rats. In Wistar-Kyoto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 56 publications
1
26
0
Order By: Relevance
“…Another important finding of our study is that calcineurin inhibition augments NMDAR activity at both presynaptic and postsynaptic sites in the PVN to cause hyperactivity of PVN presympathetic neurons. This is supported by our findings that the NMDAR-mediated 25,27,29 The increased presynaptic glutamate release subsequently acts on postsynaptic NMDARs and AMPARs to increase the excitability of PVN presympathetic neurons in CIH. Thus, NMDARs and AMPARs have overlapping roles in augmenting glutamatergic input in the PVN in CIH.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Another important finding of our study is that calcineurin inhibition augments NMDAR activity at both presynaptic and postsynaptic sites in the PVN to cause hyperactivity of PVN presympathetic neurons. This is supported by our findings that the NMDAR-mediated 25,27,29 The increased presynaptic glutamate release subsequently acts on postsynaptic NMDARs and AMPARs to increase the excitability of PVN presympathetic neurons in CIH. Thus, NMDARs and AMPARs have overlapping roles in augmenting glutamatergic input in the PVN in CIH.…”
Section: Discussionsupporting
confidence: 75%
“…Presynaptic NMDARs in the PVN are latent and not functionally active under normotensive conditions, but they become tonically activated to potentiate synaptic glutamate release in hypertensive conditions. 25,27,29 The increased presynaptic glutamate release subsequently acts on postsynaptic NMDARs and AMPARs to increase the excitability of PVN presympathetic neurons in CIH. Thus, NMDARs and AMPARs have overlapping roles in augmenting glutamatergic input in the PVN in CIH.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we found that GluA1/GluA2, but not GluA2/GluA3, heteromers were reduced in hypothalamic synaptosomes in SHR, which likely accounts for increased CP-AMPARs in hypertension. We have shown previously that α2δ-1 is upregulated and mediates potentiated synaptic NMDAR activity of PVN presympathetic neurons in hypertension Zhou, Shao, et al, 2021).…”
Section: Discussionmentioning
confidence: 87%
“…In contrast, α2δ-1 seems to favor the assembly of GluA1 homotetramers by preferentially inhibiting GluA1/GluA2 heteromeric assembly in the ER, thereby facilitating synaptic incorporation of CP-AMPARs (Li et al, 2021). Accordingly, α2δ-1 has a remarkable ability to synergistically augment Ca (Zhou, Shao, et al, 2021). α2δ-1CT peptide likely attenuates synaptic activity of both NMDARs and CP-AMPARs in SHR, because the C terminus of α2δ-1 is essential for α2δ-1 interaction with AMPARs and NMDARs (Li et al, 2021;Chen et al, 2018).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation